Analysis of Accounting Information Systems on the Effectiveness of Receivables - Eyzariyah, Eriekah; Afiqoh, Nyimas Wardatul (Indonesian Vocational Research Journal, 2025)
This study aims to analyze the role of accounting information systems on the effectiveness of accounts receivable collection at PT. X. The background of this research is based on the importance of the accounting information system in supporting the smooth billing process, especially in companies that implement a credit sales system. Even though the company has used an integrated system in managing receivables, there are still various obstacles such as data mismatches when making invoices, incomplete supporting documents, and late payments from customers. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the accounting information system implemented has helped speed up the recording process, improve data accuracy, and facilitate the process of monitoring and collecting receivables. However, the effectiveness of the system is not optimal because there are still input errors and weak document control. Therefore, the company needs to improve internal control and ensure the completeness and accuracy of data so that the accounting information system can function optimally in supporting the effectiveness of accounts receivable management. Keywords: Accounting Information System; Accounts Receivable